The Implementation of Curriculum 2013 in Teaching Speaking Skill At MAN 2 Bima - Fujiati, Hikmah; Hartono, Rudi; Wuli Fitriati, Sri (Universitas Negeri Semarang, 2020)
The aim of this research was to investigate how the implementation of curriculum 2013 in teaching speaking skill at MAN 2 Bima. This research was qualitative method and used three English teachers who taught at MAN 2 Bima. The data of this study were collected through interview, questionnaires, observation, video recording, and document analysis. Then, they were classified and analysed qualitatively. The results of the research showed that all teachers implemented the Curriculum 2013 in teaching speaking and fulfill the criteria. The findings showed that firstly the implementation of curriculum 2013 in preparing the syllabus revealed that there were three English teachers were able in developing and arranging the syllabus in accordance with the 2013 Curriculum. Second, the implementation of using the lesson plan showed that 90% had been implemented in the teaching and learning activity. Third, the implementation of the materials showed that 91,74% was done well. Third, the implementation of using media was very effective because it made the students easy to understand the materials or the lesson and the teachers were also easy to deliver the lesson. Fourth, the implementation of technique in teaching speaking using observation checklist showed that 86.66% indicators applied well. Last, The implementation of assessment and evaluation used the observation checklist showed that 82,85% of indicators were applied well. So, from the all result above, it was concluded that the activities of implementing the curriculum 2013 in teaching speaking skill by the English teachers were appropriate with the standard of 2013 Curriculum.